Water user participation in Egypt: an incremental process towards irrigation management transfer - El-Sharkawy, Moamen, author; El-Diasty, Amira, author; Wassief, Khaled, author; Viala, Eric, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
Experiences establishing Water User Associations (WUAs) in Egypt have been carried out for the past 15 years, with increasingly promising results. Most of these activities have been pilot projects aiming to demonstrate the benefits and sustainability of WUAs. They were consequently implemented through a centralized and resource-intensive process and focused on limited numbers of associations. Since 2003, the Ministry of Water Resources and Irrigation (MWRI) has adopted as policy the large-scale development of Branch Canal WUAs. With support from USAID, about 600 branch canal WUAs (BCWUAs) have since been established, covering 15% of Egypt's irrigated area and involving half a million farmers and residents. In order to achieve this impressive outcome, a different approach has been developed and implemented, emphasizing the direct involvement of MWRI field staff and a partnership between water users and MWRI managers. This paper also argues that the conventional approach of forming WUAs by focusing on water users, and empowering them to take over the O&M responsibilities of irrigation systems, is not adapted to the Egyptian context.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.